Pro Zend framework techniques build a full CMS project - Lyman, Forrest; Safari eBooks ([Berkeley, Calif.] : Apress ; New York : Distributed to the book trade worldwide by Springer-Verlag New York, 2009)
"One of the most common uses for a framework such as this is to build content-driven web sites. Pro Zend Framework CMS provides a clear guide to building a custom CMS with the Zend Framework, showing how to utilize the many different aspects of the framework as part of the process"--Resource description page.
Description based on print version record.
Includes index.
Keywords: Open source software; PHP (Computer program language); Electronic books